RANCANG BANGUN DASHBOARD SYSTEM UNTUK PEMANTAUAN JOBSEEKER (ALUMNI) PADA PUSAT LAYANAN KARIR DAN ALUMNI (PLKA) UNIVERSITAS DINAMIKA - Saputra, Ibnu Pratama Adi; Nurcahyawati, Vivine; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
The Career and Alumni Service Center (PLKA) is a career development center that aims to become a liaison between companies and job seekers, especially those from Undika. PLKA has several work programs to connect companies with job seekers. But at this time, a problem was found, namely the absence of a supporting application that could monitor alumni looking for work or jobseekers (alumni). Based on these problems, in this research, a dashboard system application was made to make it easier for PLKA to monitor jobseekers (alumni). In building a dashboard system application for PLKA using the Waterfall System Development Life Cycle (SDLC) method. The result of this research is that this application can help PLKA find out information related to monitoring the number of alumni applying for job vacancies, the number of applicants based on activities, the number of job vacancies, and the number of graduate competency promotion activities in real-time and can determine the value of the KPI indicator used as a comparison target with actual achievements. In this way, this application can be used as a basis for decision making in higher education management for determining higher education strategies related to career development.Keywords: PLKA, Dashboard System, Monitoring Jobseeker, Alumni